Metaphor as Creativity in Audio Descriptive Tours for Art Museums: From Description to Practice - Luque Colmenero, María Olalla; Soler Gallego, Silvia (Journal of Audiovisual Translation, 2020)
In a previous corpus-based descriptive study, we concluded that a linguistic metaphor is a frequently used technique in audio description (AD) for art museums and proposed a set of categories to describe this resource. These results led us to compose increasingly creative and subjective ADs for a series of audio descriptive guided tours of art exhibitions carried out within the Words to See accessibility project. In the present study, the same categories are applied to the analysis of the ADs created for these guided tours. In these ADs, metaphors are used to describe both representational and abstract art, while some categories of deliberate metaphor are more frequently used to describe abstract works. These results are discussed in relation to our and other authors’ studies in this field, as well as to theories of art education and gallery teaching.